How can vacant properties be used to revitalize North St. Louis City? - Johnson, Darrell (Kansas State University, 2022)
Cities in the United States have long been afflicted by the impacts of vacant commercial and residential properties. Buildings that once held purpose now sit empty and abandoned. Properties can be vacant for several reasons, including abandonment, fire, displacement, foreclosure, or other causes. Following the recession of 2009, a spike in vacancy spread across the nation as foreclosures surged and led to disinvestment, crime, decreased property values, and lost tax revenue. These issues cost cities and municipalities millions of dollars annually for policing, maintaining, and demolishing vacant buildings. Although vacant properties are a challenging issue, cities, residents, and organizations across the U.S. are taking action to address vacancy. In recent years, cities and local organizations have looked to improve the social and economic dimensions of neighborhoods by rehabilitating and repurposing vacant properties. This study aims to support the efforts of rehabilitating and repurposing vacant properties in North St. Louis City. By analyzing the present situation of vacant properties in Ward 27 and surveying the community, this study explores the challenges faced by the community, and how these properties can be repurposed to meet the needs of current and future residents. It was found that most of the respondents prefer reinvestment in the community and lack of funding is one of the key barriers for reusing vacant properties. They prefer purchase and restore of vacant properties over demolition, and in case of vacant lots, they prefer new construction over other uses. An area of the neighborhood is identified where any funding assistance should be targeted considering surrounding land uses and current needs of the community.
Keywords: Vacancy; Revitalization; Vacant property; St. Louis; Population decline